Estudio de prefactibilidad para la instalación de una planta de producción de pasta dental natural a base de aceite de coco - Flores Chacon, Zaira Joeni (2022)
The following research work’s purpose is to determine the feasibility of the installation of a natural toothpaste production plant based on coconut oil which, through nine chapters written, allowed to confirm the profitability of the project. The product will be commercialized under the name “Fluoral”, in 75 mg aluminum tubes, which will be sold to the public in individual ecological containers to promote a culture of using natural products. After two years of research, and an initial survey of 266 individuals within the target population, it was determined that, with an acceptance rate of 56,7%, the demand for the project for the first year would be 805 840 units of toothpaste. This is detailed in the second chapter, where a rigorous analysis of the market to be entered was made and we can also find the marketing, promotion and distribution plan for the product. Likewise, through the ranking of factors method, it was concluded that the best location for the construction of the plant would be in Lurin, which is detailed in chapter three. On the other hand, in chapter four, the plant size was found after comparing the market size, technology, productive resources and break-even point. Then, the production process was evaluated in chapter five, in which it was determined that the engineering required to manufacture the product will be done under a semi-automatic process. Finally, for the financial evaluation, chapter seven detailed the economic and financial aspects that allowed obtaining NPV and IRR as main indicators, which presented healthy values within the parameters to define a project as financially profitable, and a payback period of three years, two months and twelve days was obtained.